2022
DOI: 10.1093/jas/skac175
|View full text |Cite
|
Sign up to set email alerts
|

Increased supply of methionine during a heat-stress challenge in lactating holstein cows alters mammary tissue mTOR signaling and its response to lipopolysaccharide

Abstract: The first objective was to investigate the effects of feeding rumen-protected methionine (RPM) during a heat stress (HS) challenge on abundance and phosphorylation of mechanistic target of rapamycin (mTOR)-related signaling proteins in mammary gland. The second objective was to investigate how HS and RPM may modulate the response of mammary gland explants to lipopolysaccharide (LPS) stimulation. Thirty-two multiparous, lactating Holstein cows (184 ± 59 DIM) were randomly assigned to 1 of 2 environmental treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In the current experiment, we found increased plasma insulin concentrations during heat stress which was reverted in HS+AA by the end of the experimental period along with the recovery of milk protein content and decrease of milk urea (Ruiz-Gonzaĺez et al, 2022a). Lastly, Met was also suggested to activate the mTOR pathway in the mammary gland, however, the exact mechanisms are not yet known (Coleman et al, 2022). Our results indicated that improved milk protein content in HS+AA was associated with the increased availability of EAA, however, the exact interactions between Lys, BCAA, Met and the mTOR pathway are yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the current experiment, we found increased plasma insulin concentrations during heat stress which was reverted in HS+AA by the end of the experimental period along with the recovery of milk protein content and decrease of milk urea (Ruiz-Gonzaĺez et al, 2022a). Lastly, Met was also suggested to activate the mTOR pathway in the mammary gland, however, the exact mechanisms are not yet known (Coleman et al, 2022). Our results indicated that improved milk protein content in HS+AA was associated with the increased availability of EAA, however, the exact interactions between Lys, BCAA, Met and the mTOR pathway are yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 74%
“…Under heat-stress conditions, milk yield and oxidative status of dairy cows was improved by increased Met supply, rather than MP (Mesgaran et al, 2022). In vitro studies on hyperthermic mammary gland epithelial cells indicated that increased Met supply can lead to a higher synthesis of the antioxidants taurine and glutathione and stimulate protein synthesis through the direct activation of the mechanistic target of rapamycin (mTOR) pathway or indirectly by increased branched-chain AA (BCAA) availability (Dong et al, 2018;Lopreiato et al, 2020;Coleman et al, 2022). However, the improved productive performance of heat-stressed cows after dietary Met supplementation was not consistent across the few reported studies (Pate et al, 2020;Mesgaran et al, 2022) and the mechanisms and pathways remain to be understood (Lopreiato et al, 2020;Mesgaran et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As such, it plays a pivotal role in epigenetics via DNA methylation [ 20 ] and forms a key part in the one-carbon metabolism in its biologically active form of S-adenosyl-methionine. Via the trans-sulfuration pathway and the intermediate metabolite cysteine, it is involved in the synthesis of the antioxidants glutathione and taurine [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that due to maternal methionine supply neonatal calves experienced beneficial effects on their antioxidant status. The supplementation of RPMET to peripartal dairy cows also led to an improved antioxidant status [ 21 , 36 , 37 ]. Alfaro et al [ 38 ] conducted a nutrigenetics study in beef cattle.…”
Section: Discussionmentioning
confidence: 99%